PENGARUH KONFLIK, STRESS DAN PERUBAHAN ORGANISASI TERHADAP PRODUKTIVITAS KARYAWAN - Rafnelly Rafki; Hafidz Aima; Lusiana Lusiana; Silvia Sari; Yolanda Oktarina; Nofriadi Nofriadi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
Employee well-being is an important factor in the productivity and success of an organization. Conflict can cause stress, and job dissatisfaction and affect employee welfare. Protracted conflicts or damaging relationships between employees can hinder operational efficiency. There has been much study of the effects of conflict and stress, but not much has been studied about the effect of conflict and stress and organizational change on employee productivity. The purpose of this study is to study the effect of conflict, stress, and organizational change on employee productivity. This research is a survey research with data collection of 300 respondents through questionnaires and interviews. Questions in the survey include the level of conflict experienced, its impact on productivity, and the factors that influence it. There are 3 independent variables, namely conflict, stress, and organizational change. Its dependent variable is productivity. Linear regression or multiple regression is used to identify the extent to which conflict, stress, and organizational change predict productivity. Also used analysis with SEM. The results showed that the level of conflict in the workplace had a significant negative impact on employee productivity. The level of stress experienced by employees is also related to productivity. High stress leads to a decrease in productivity. Organizational change contributes to higher levels of conflict and stress among employees. However, managing change with good communication and management support can reduce the negative impact of change on productivity. This study concludes that good conflict management, stress management, and effective change management can help increase employee productivity in the work environment. The conclusion of this study provides a foundation for actions and policies that support increased employee productivity in the work environment.